Changes in approach to customer loyalty - Katarzyna Szczepańska; Patryk Paweł Gawron (Contemporary Economics, 2011)
The article discusses an overview of customer loyalty theoretical framework. It presents both, the classic approach to the subject of loyalty as well as the results of its ongoing evolution. This allowed the identification of factors affecting customer loyalty and a statement that the concept of loyalty can be seen in varying degrees, in terms of criteria other than behavioral. Finding of not enough empirical research on customer loyalty in the long types of market and specific customer groups indicates a cognitive gap. Verification of the classic determinants of customer loyalty authorized to conclude that the profitability of the customer portfolio sets new definition of loyalty, which is related to the concepts of marketing value and value based management. This is supported by associations of loyalty to the management parameters.
Keywords: L19; L53; M31; 330; customer and business loyalty; marketing value; customer portfolio